2007
DOI: 10.1093/her/cym047
|View full text |Cite
|
Sign up to set email alerts
|

Moderators and mediators of behaviour change in a lifestyle program for treated hypertensives: a randomized controlled trial (ADAPT)

Abstract: We aimed to examine moderators and mediators of behaviour change in a cognitive lifestyle program for drug-treated overweight hypertensives in Perth, Australia. We collected data at baseline, 4 months (post-intervention) and 1-year follow-up in a randomized controlled trial of a program that focused on weight loss, diet, and exercise. Mediation analysis used regression models that estimate indirect effects with bootstrapped confidence limits. Outcomes examined were saturated fat intake (% energy) and physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 29 publications
7
42
3
Order By: Relevance
“…From the total 13 included studies, eight were found a direct association between self-efficacy and specific health behaviours (Berendes & Rimal, 2011;V. Burke et al, 2007;Chariyeva et al, 2013;Ievers-Landis et al, 2003;Luszczynska, 2004;Morisky et al, 2001;Piaseu et al, 2002;Strathdee et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the total 13 included studies, eight were found a direct association between self-efficacy and specific health behaviours (Berendes & Rimal, 2011;V. Burke et al, 2007;Chariyeva et al, 2013;Ievers-Landis et al, 2003;Luszczynska, 2004;Morisky et al, 2001;Piaseu et al, 2002;Strathdee et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Another randomized controlled trial of a cognitive lifestyle program for drug-treated overweight hypertensive patients in Perth, Australia reported that change in self-efficacy mediated change in saturated fat consumption (effect size (ES) -0.055, 95% CI (-0.125, -.005) at post intervention and (ES -0.054, 95%CI ;0.127, -0.005) at the follow up (V. Burke, Beilin, Cutt, Mansour, & Mori, 2007). Self-efficacy also explained change in time spent in exercise at least moderate intensity at post intervention (ES 0.059, 95% CI; 0.003, 0.147).…”
Section: Self-efficacy and Non-communicable Disease Controlmentioning
confidence: 99%
“…In this study neither perceived family social support nor friend social support moderated the effect of gender, BMI, income adequacy, and religious commitment on DFI. Similarly, Burke et al (2008) did not find a significant interaction of social support for dietary fat intake; but the sample consisted of adults ranging from 40 to 70 years old. It may be possible that a statistically significant interaction between perceived family social support and perceived friend social support with BMI, income adequacy, and religious commitment was not found because the sample in this current study was homogeneous, which "may weaken detection of a moderator effect" (Bennett, 2000, p. 418).…”
Section: Research Questionmentioning
confidence: 87%
“…No studies were found for religious commitment. As for the moderating effects of social support, with dietary fat intake as the dependent variable, only one study, with a sample of adults ages 40-70, has been conducted by Burke et al (2008). This is the first study, to date, to examine the potential moderating effects of religious commitment and social support in regards to dietary fat intake among Black emerging adults.…”
Section: Modifying and Mediating Factors Of Dfimentioning
confidence: 99%
“…Burke et al 8) describe the gender-related variances of the effect of diet control and exercises on saturated fat intake and physical Activities of overweight and hypertensive patients treated with drugs and point out that the involvement of diet control and exercises increases the self-efficacy and affect the saturated fat intake and physical Activities. In this case, gender is a moderator, and self-efficacy is a mediator.…”
Section: Introductionmentioning
confidence: 99%